The Implementation of Independent Learning Activity Units in the Semester Credit System Improves Learning Achievement - May (International Journal Education and Computer Studies (IJECS), 2022)
The purpose of this study was to find out how much contribution the application of the Independent Learning Activity Unit in the Semester Credit System to the Learning Achievement of Students at the Doyo Baru Adventist High School contributed. This study uses quantitative methods with a correlational research design approach. Based on the result of the study, there is a significant relationship between independent learning activity units in the semester credit system and learning achievement the is a correlation coefficient value (R) = 0.685; coefficient of determination (R2) = 0.469. The results of this study indicate the relationship between the application of the Independent Learning Activity Unit in the Semester Credit System and the Student Achievement of 46.9%. The remaining 53.1% contributed by other variables not examined in this study. The contribution of the Independent Learning Activity Unit from the Implementation of the Independent Learning Activity Unit in the Semester Credit System to the Student Achievement of 46.9%.